Short sellers and corporate disclosure - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2018)
We examine how short sellers affect corporate disclosures using a natural experiment. From May2005 to July 2007, the SEC implemented a pilot program by randomly selecting one third ofRussell 3000 stocks and removing the short sale price tests for these stocks (referred to as pilotfirms), leading to lower short-selling constraint, without changing the requirement for other firms(referred to as control firms). We compare the change in corporate disclosures between the pilotfirms and the control firms during this period. We find that compared to the control firms, thepilot firms are more likely to issue good news management forecasts without changing theissuance of bad news forecasts. We also find that the decrease in short-selling constraint for thepilot firms (1) leads to an increased likelihood of bundling bad news forecasts with good newsearnings announcements, and (2) does not lead to an increase in the optimistic bias inmanagement forecasts. Overall, our evidence suggests that the reduction in short-sellingconstraint motivates managers to disclose good news in a more timely fashion.